THERE IS THE USE OF TRADITIONAL METHODS OF TREATMENT FOR HELP БІОЛОГІЧНОАКТИВНИХ OF ADDITIONS - Сліпцова, Наталія; Коваленко, Поліна; Євстигнєєва, Анастасія; Тур, Ярослава (SWorldJournal, 2023)
Lately interest grows in M in relation to his general influence on the processes of exchange, positive influence on the function of organs and systems of organism. There is an idea, that application of preparations of M does not object the traditional met